Reluctant subjects or passive resistance? A commentary on J. K. Gibson-Graham's "Surplus possibilities: Postdevelopment and community economies" - Curry, George (Blackwell Synergy, 2005)
A commentary on J.K. Gibson-Graham's "Surplus possibilities: Postdevelopment and community economies"